Qualities of rice in Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The yield of African rice Oryza Glaberrima may be lower than Asian varieties, which might explain why breeders seem to have neglected it. It has more than just its preferred taste going for it. One unexplored quality to have caught the eye of the...